2022
DOI: 10.1186/s13023-022-02407-5
|View full text |Cite
|
Sign up to set email alerts
|

Parents as informal caregivers of children and adolescents with spinal muscular atrophy: a systematic review of quantitative and qualitative data on the psychosocial situation, caregiver burden, and family needs

Abstract: Background Spinal muscular atrophy (SMA) is a rare degenerative neuromuscular disease, mostly occurring in infants and children, leading to muscle wasting and weakness, and premature death. Due to new developments of multiple disease-modifying treatments within the last years, the interest of research in patients affected by SMA increased steadily. However, the psychosocial situation of parents as informal caregivers is still rarely addressed. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 84 publications
1
21
0
Order By: Relevance
“…This is the first study in France to examine how parents of children with SMA type 1 experience the decision-making process around innovative therapy for their child. The participants in our study were mainly mothers, which is consistent with participation rates found in the literature ( 24 ). The average age of parents in our study is slightly higher than the average age reported in the only other study providing information on the age of parents of children with type 1 SMA ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is the first study in France to examine how parents of children with SMA type 1 experience the decision-making process around innovative therapy for their child. The participants in our study were mainly mothers, which is consistent with participation rates found in the literature ( 24 ). The average age of parents in our study is slightly higher than the average age reported in the only other study providing information on the age of parents of children with type 1 SMA ( 25 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we did not measure parental responsibility quantitatively as we felt there were no relevant tools to do so. Brand et al point out that studies based on quantitative methodologies report an average to moderate burden ( 24 , 26 – 29 ) in parents of children with SMA. However, these studies used the Zarit scale or the Caregiver Strain index, scales initially developed to assess the burden of caregivers of patients with dementia and/or the elderly and which have not been validated in a population of parents of children with degenerative diseases ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, QoL was relatively poor in children with type I and type II SMA as well as in their caregivers compared to those with SMA type III [ 32 ]. Further, the clinical relevance of reported disturbances of QoL in caregivers should support the implementation of adequate support services for families of symptomatic SMA patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%